Extracellular Chromatin Triggers Release of Soluble CEACAM8 Upon Activation of Neutrophils - Ribon, Matthieu; Mussard, Julie; Semerano, Luca; Singer, Bernhard B.; Decker, Patrice (Frontiers in Immunology, 2019)
Increased concentrations of extracellular chromatin are observed in cancer, sepsis and inflammatory autoimmune diseases like systemic lupus erythematosus (SLE) or rheumatoid arthritis (RA). In SLE and RA, extracellular chromatin may behave as a danger-associated molecular pattern (DAMP). Polymorphonuclear neutrophils (PMN) are described as typical pro-inflammatory cells but possess also immunoregulatory properties. They are activated in SLE and RA but surprisingly remain moderately studied in these diseases, and especially the disease-associated stimuli triggering PMN activation are still not completely characterized. PMN express plasma membrane carcinoembryonic antigen-related cell adhesion molecule (CEACAM) 8 (CD66b) and secrete a soluble form of CEACAM8 after activation. Soluble CEACAM8 has in turn immunoregulatory functions. However, few natural stimuli inducing soluble CEACAM8 secretion by PMN have been identified. Here we demonstrate for the first time that extracellular chromatin triggers secretion of soluble CEACAM8 by primary human PMN. Priming of PMN was not required. Secretion was associated with activation of PMN. Similar induction of soluble CEACAM8 release was observed with purified mono-nucleosomes as well as long chromatin fragments and occurred in a time-dependent and concentration-dependent manner. Results indicate that chromatin induces both neo-synthesis of soluble CEACAM8 and release of soluble CEACAM8 through degranulation. In addition, we report the presence of soluble CEACAM8 at high concentration in the synovial fluid of RA patients. Thus, we describe here a novel mechanism by which a natural DAMP, with inflammatory properties in SLE and RA, induces soluble CEACAM8 secretion by activated PMN with potential immunoregulatory consequences on other immune cells, including PMN.